2020
DOI: 10.1111/rec.13309
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of remotely sensed environmental drivers on coral outplant survival

Abstract: Globally, coral reefs are degrading due to a variety of stressors including climate change and pollution. Active restoration is an important effort for sustaining coral reefs where, typically, coral fragments are outplanted onto degraded reefs. Coral outplants, however, can experience mortality in response to a range of stressors. We pair results of outplant monitoring observations with satellite‐based measurements of multiple oceanographic variables to estimate the relative importance of each driver to coral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…As such, work is needed to scale up these approaches if they are to have a meaningful impact on coral reef resistance to ocean warming. However, this approach cannot work in isolation, and it is imperative that investments in adaptive management are supported by strong local measures to maintain water quality and limit overfishing ( 61 , 62 ). In addition, these measures cannot replace global measures urgently needed to reduce carbon emissions and slow the intensification of climate change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, work is needed to scale up these approaches if they are to have a meaningful impact on coral reef resistance to ocean warming. However, this approach cannot work in isolation, and it is imperative that investments in adaptive management are supported by strong local measures to maintain water quality and limit overfishing ( 61 , 62 ). In addition, these measures cannot replace global measures urgently needed to reduce carbon emissions and slow the intensification of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Site selection for nurseries and outplanting is also an important consideration to maximize restoration success, as water quality is critical for outplant survival ( 62 ) and can be managed at the local level. Here, we found that the reef with the greatest water flow, diel physicochemical variation, and distance from land resulted in higher coral growth and fitness.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not necessarily demonstrate inadequate preparation-dedicated surveys of environmental conditions, and in particular of coral recruitment, are costly and time-consuming, and relevant information may be gathered from individuals familiar with the local environment or from public sources. For example, remote sensing data on particulate matter or sea surface temperature fluctuations can help to identify sites with higher potential for transplant survival and resilience to future disturbance [58,59]. Lastly, while the need for baseline surveys prior to restoration is highly relevant [60] and better management and water quality standards remain important, they should not be considered excuses for foregoing attempts at saving remaining diversity and resilience.…”
Section: Assessment Of Reef Conditionmentioning
confidence: 99%
“…For instance, measuring Sea Surface Temperatures (SST) have helped to draw conclusions that corals have already started adapting to the rise of ocean temperature [17]. Similarly, as anomalies in SST are an important factor in coral outplant survival [210], an algorithm forecasting SST can predict which heat stress may cause a coral bleaching event [211]. Furthermore, it is possible to use deep neural networks to predict SST even more accurately [212].…”
Section: Indirect Sensingmentioning
confidence: 99%